Accelerating Progress Model (AP Model) in the SDGs Implementation – a Chance to Achieve 2030 Agenda Goals Under COVID-19 Conditions - Katarzyna CHŁAPEK; Sylwia KRAJEWSKA (Communications of International Proceedings, 2020)
The implementation of 2030 Agenda with respect to social, environmental and economic issues is of key significance for the future of our planet and requires the current engagement of all the inhabitants of the Earth. All these aspects play a special role in the context of the COVID-19 pandemic, hence the need for assessing the SDGs progress with a view to adapting activities in this area to the present circumstances. The analysis presented in the paper points to an insufficient level of communicating SDG-related actions, particularly at the stage of sharing and disclosing good practices. Another issue is the lack of adequate and user-friendly measuring tools, facilitating the determination of the progress in the SDGs implementation by various stakeholders. The paper aims to present a model for accelerating the SDGs implementation (AP model), based on the verification of good practices related to the goals as well as an analysis of COVID-19 implications. The major advantage of the AP model is its simplicity as a measuring tool, which serves to strengthen an entity’s sense of contribution to the achievement of 2030 Agenda. The paper stresses the necessity of undertaking further research on the possibility of measuring an individual company’s impact on achieving Agenda goals. The awareness and knowledge of the impact of specific actions on the quality of life of future generations can accelerate the SDGs implementation. The conclusions presented in the paper may be put into practice by various groups of 2030 Agenda stakeholders, as well as stimulate further research at an academic level.
Keywords: MDGs; SDGs; COVID; good practices